1996
DOI: 10.1021/jm950642a
|View full text |Cite
|
Sign up to set email alerts
|

Development of Highly Potent Inhibitors of Ras Farnesyltransferase Possessing Cellular andin VivoActivity

Abstract: Analogs of CVFM (a known nonsubstrate farnesyltransferase (FT) inhibitor derived from a CA1A2X sequence where C is cysteine, A is an aliphatic residue, and X is any residue) were prepared where phenylalanine was replaced by (Z)-dehydrophenylalanine, 2-aminoindan-2-carboxylate, 1,2,3,4-tetrahydroisoquinoline-3-carboxylate (Tic), and indoline-2-carboxylate. The greatest improvement in FT inhibitory potency was observed for the Tic derivative (IC50 = 1 nM); however, this compound was ineffective in blocking oncog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
48
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 31 publications
2
48
0
Order By: Relevance
“…The fact that prenylation is required for the oncogenic activity of small GTPases prompted us and others to design FTase and GGTase I inhibitors (FTIs and GGTIs) as potential anticancer drugs (14,26,35,57). While numerous studies have shown that FTIs suppress oncogenic and tumor survival pathways, the actual mechanism by which FTIs inhibit tumor growth is not known (34,44).…”
mentioning
confidence: 99%
“…The fact that prenylation is required for the oncogenic activity of small GTPases prompted us and others to design FTase and GGTase I inhibitors (FTIs and GGTIs) as potential anticancer drugs (14,26,35,57). While numerous studies have shown that FTIs suppress oncogenic and tumor survival pathways, the actual mechanism by which FTIs inhibit tumor growth is not known (34,44).…”
mentioning
confidence: 99%
“…BMS initiated their pursuit of protein competitive FTIs with peptidomimetics of the CAAX box [44][45][46] and claimed their first non-peptide class of FTIs, including BMS-214662, in 1997 [132]. A related class containing 1,2,5-benzothiadiazepine-1, 1-dioxides with N-2 imidazolylalkyl substituents [133] was reported in 2000.…”
Section: Imidazole-containing Compoundsmentioning
confidence: 99%
“…More extensive structure-activity studies showed the analog Cys-Val-Phe-Met to be the most potent inhibitor among 42 CXXX analogs, where X stands for all the possible natural amino acids (17). Subsequent reduction of selected amide bonds in CA 1 A 2 X-based inhibitors Jed to a significant improvement of the inhibitory potency and activity in whole cells (18). Similarly, analogs containing confonnationally constrained amino acid residues were also shown to be potent inhibitors (19).…”
Section: Introductionmentioning
confidence: 96%
“…Accordingly, the conformational profiles of a small set of CA 1 A 2 X-based inhibitors (18), with A 2 being an confonnationally constrained aromatic amino acid residue, were compared in order to assess the conformational requirements of the Ff inhibitors. Specifically, two active and two inactive inhibitors were selected for the present study: the active analogs Cys-Val-Tic-Met (1) and Cys-Val-'¥(CH 2 NH)TicMet (2) and the inactive analogs Cys-Val-Tic-'¥(CH 2 NH)Met (3) and Cys-Val-AicMet (4), where Tic and Aic are the unnatural amino acid residues (S)-1,2,3,4-tetrahydroisoquinoline-3-carboxylate and 2-aminoindane-2-carboxylic acid, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation